Instruments in Motion: Flutes, Harmonicas and the Interplay of Sound and Silence in Colonial Micronesia - Diettrich, Brian (Waka Kuaka, 2017)
This article explores musical instruments in colonial Micronesia in their sonic, material and historical contexts. Using archival and oral sources and museum artefacts this study investigates the movements of instruments, including the abandonment of some and the acceptance of other types within Micronesian communities in the late 19th and early 20th centuries. The study argues for critical attention to the interplay of sound and silence within imperial enterprises in the Pacific, and it addresses the agency of musicians and listeners within a musical and material modernity. Specifically, this study also provides the first in-depth, comparative investigation of indigenous flutes from the Caroline Islands, as well as the first detailed cultural study of nose flutes from Chuuk in the Federated States of Micronesia. Through the investigation of historical flutes and colonial-derived instruments such as the harmonica I query how we understand the movements of things in their material and aesthetic forms, and I argue for the role of musical instruments in the unfolding of Pacific pasts and presents.